2022
DOI: 10.4018/ijaci.293111
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Adversarial Mechanisms in Deep Neural Networks

Abstract: Deep learning is a subspace of intelligence system learning that experienced prominent results in almost all the application domains. However, Deep Neural Network found to be susceptible to perturbed inputs such that the model generates output other than the expected one. By including insignificant perturbation to the input effectuate computer vision models to make an erroneous prediction. Though, it is still a dilemma whether humans are prone to comparable errors. In this paper, we focus on this issue by leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Pavate et al [20] discussed the different adversarial generations using gradient-based methods and concluded that calculating the gradient is practically difficult. Evolutionary algorithms (EAs) have been used to generate hostile examples.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Pavate et al [20] discussed the different adversarial generations using gradient-based methods and concluded that calculating the gradient is practically difficult. Evolutionary algorithms (EAs) have been used to generate hostile examples.…”
Section: Related Workmentioning
confidence: 99%
“…The previous work concentrates on generating adversarial samples using gradient optimization methods that need internal design aspects of the model, such as several parameters for training, training data, and neural network type [6] [19]. Several adversarial samples are created without understanding the model's essential details, like the internal organization of the model [9] [20]. Evolutionary algorithms work only on the probability of labels from the target model; no internal details are required.…”
Section: Introductionmentioning
confidence: 99%